Beginning Database-Driven Application Development in Java EE Using GlassFish - Vasiliev, Yuli.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
Beginning Database-Driven Application Development in Java™ EE: Using GlassFish™ focuses on the open source GlassFish persistence engine. This book shows Java programmers how to develop applications utilizing relational database technologies with examples using Oracle and MySQL and the GlassFish application development framework and deployment platform all based on Java EE. The book explains in detail how you can organize your Java EE solution into a multilayer architecture, placing most emphasis on how to implement the persistence and database tiers of an application. Through many examples, this book shows how you can efficiently use the Java Persistence features available in the Java EE platform. Find out how you can greatly simplify the task of building the persistence layer of your Java EE application by moving some application logic into the underlying database, utilizing database views, stored programs, and triggers. The book also explains how to deploy Java EE applications to GlassFish, a free, open source Java EE 5–compliant application server.
Setting Up Your Working Environment -- Getting Started with GlassFish -- Introducing EJB 3 and the Java Persistence API -- Planning the Application -- Planning a Java EE Application -- Planning the Underlying Database -- Building the Database Tier -- Implementing the Database Tier -- Setting Up the Data Source -- Building the Persistence Tier -- Designing JPA Entities -- Object/Relational Mapping -- Using EntityManager -- Using Java Persistence Query Language (JPQL) -- Building the Business Logic Tier -- Designing Session Beans -- Managing Transactions -- Building the Presentation Tier and Testing -- Building the Presentation Tier -- Testing the Application.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems